Germinative potential and leaf morphoanatomy of physic nut seedlings from cryopreserved germplasm - Silva, Rafael de Carvalho; Camillo, Julceia; Luis, Zanderluce Gomes; Scherwinski-Pereira, Jonny Everson (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the germinative potential and the morphoanatomical features of leaves in seedlings of physic nut from cryopreserved germplasm. Initially, seeds were evaluated regarding desiccation every 24 hours for up to 120 hours. Then, seeds were desiccated for 0, 24, and 48 hours, and evaluated monthly as to germinative potential, before and after storage in liquid nitrogen by direct immersion and fast freezing. To characterize the viability of seeds that did not germinate after the evaluation period, the zygotic embryos were immersed in tetrazolium solution. Morphoanatomical features of leaves were determined after cryopreservation by histological evaluation. Physic nut seeds tolerated desiccation to critical levels and cryopreservation with moisture content around 8%. Seed desiccation to lower values, associated with longer periods of exposition to liquid nitrogen, causes abnormalities in seedlings, damages leaf cells and tissues, and affects negatively germination.